2020
DOI: 10.1088/1361-6382/ab6f7f
|View full text |Cite
|
Sign up to set email alerts
|

Extended FLRW models: dynamical cancellation of cosmological anisotropies

Abstract: We investigate a corner of the Bianchi models that has not received much attention: "extended FLRW models" (eFLRW) defined as a cosmological model with underlying anisotropic Bianchi geometry that nevertheless expands isotropically and can be mapped onto a reference FLRW model with the same expansion history. In order to investigate the stability and naturalness of such models in a dynamical systems context, we consider spatially homogeneous models that contain a massless scalar field ϕ and a non-tilted perfec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
(168 reference statements)
0
20
0
Order By: Relevance
“…The intriguing possibility that the geometry of the Universe may not be of the standard Friedmann-Lemaitre-Robertson-Walker (FLRW) form was investigated, from different points of view, in [142][143][144][145][146][147][148][149][150][151][152][153].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intriguing possibility that the geometry of the Universe may not be of the standard Friedmann-Lemaitre-Robertson-Walker (FLRW) form was investigated, from different points of view, in [142][143][144][145][146][147][148][149][150][151][152][153].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, so-called extended FLRW models, representing a cosmological model with an underlying anisotropic Bianchi geometry that expands isotropically, and that can be mapped onto a standard FLRW model with the same expansion history, were investigated in [153]. It was found that matter and geometrical anisotropies tend to cancel out each other dynamically, and that, under rather general conditions, the expansion is asymptotically isotropic.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-know in the GR case that for Bianchi I and Bianchi III, the Hubble parameter H is always monotonic and the anisotropy decays in time for H > 0. Therefore, isotropization occurs [20]. However, for Kantowski-Sachs, as well as for closed FLRW, the Hubble parameter is not guaranteed to be monotonic, and anisotropies would increase rather than vanish (see [21,22] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…to obtain additional information. If we exploit (19) and (20) with the means to substitute two of the momenta in expression (28), we observe that the latter leads to an algebraic relation among the configuration space variables. In particular we get…”
mentioning
confidence: 99%
See 1 more Smart Citation